RNA-Seq-based analysis of changes in Borrelia burgdorferi gene expression linked to pathogenicity - Wu, Qiong (Parasit Vectors, 2015)
BACKGROUND: Lyme disease is a global public health problem caused by the spirochaete Borrelia burgdorferi. Our previous studies found differences in disease severity between B. burgdorferi B31- and B. garinii SZ-infected mice. We hypothesized that genes that are differentially expressed between Borrelia isolates encode bacterial factors that contribute to disease diversity. METHODS: The present study used high-throughput sequencing technology to characterize and compare the transcriptional profiles of B. burgdorferi B31 and B. garinii SZ cultured in vitro. Real-time quantitative RT-PCR was used to validate selected data from RNA-seq experiments. RESULTS: A total of 731 genes were differentially expressed between B. burgdorferi B31 and B. garinii SZ isolates, including those encoding lipoproteins and purine transport proteins. The fold difference in expression for B. garinii SZ versus B. burgdorferi B31 ranged from 22.07 to 1.01. Expression of the OspA, OspB and DbpB genes were significantly lower in B. garinii SZ compared to B. burgdorferi B31. CONCLUSIONS: The results support the hypothesis that global changes in gene expression underlie differences in Borrelia pathogenicity. The findings also provide an empirical basis for studying the mechanism of action of specific genes as well as their potential usefulness for the diagnosis and management of Lyme disease. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13071-014-0623-2) contains supplementary material, which is available to authorized users.